Pengaruh Metode Praktikum terhadap Hasil Belajar IPA Materi Pertumbuhan dan Perkembangbiakan pada Tumbuhan Siswa Kelas 3 SDN Cikupa III Kabupaten Tangerang - Zahrotul Muplihah; Ina Magdalena; Yayah Huliatunisa (AS-SABIQUN, 2022)
The concept of science in elementary schools is an integrated concept because it has not been separated separately, such as biology, chemistry, and physics. The low quality of education can be seen from the low quality of student learning. One of the causes of the low quality of education is due to the learning difficulties experienced by most students. This study aims to determine the differences in student learning outcomes between students who use practicum methods and students who do not use conventional practicum or learning methods. The population in this study were all class III students at SDN Cikupa III, totaling 57 students, consisting of 27 students in class III A as the control class and class III B with 30 students as the experimental class. The research used is Quasi Experimental Design. The results of the pretest calculation between the control class and the experimental class obtained a tcount value of 0.167 > 0.05, while the post-test calculation between the control class and the experimental class obtained a tcount value of 0.139 > 0.05, which causes H0 to be accepted and HI rejected. The results of this test prove that there is no influence on the learning outcomes of science learning material on growth and reproduction in the third grade students of SDN Cikupa III, Tangerang Regency.